The Rational Emotive Behavioral Therapy and Students' Defense Mechanisms - Farideh Hamidi; Farshid Paidar (Shiraz University of Medical Sciences, 2016)
Background: Defense mechanisms are psychological operations which often prevent stressful norms, beliefs, and values to emerge and reach the level of consciousness. Objectives: The aim of the present study was to investigate the effect of Rational Emotive Behavioral Therapy (REBT) on defense mechanisms of boy high school students at east Azerbaijan, Iran. Patients and Methods: This experimental study was conducted on all male students (n = 680) enrolled in the second and third grades of high school in east Azerbaijan, Iran, during 2014 - 2015. To select the sample, first the defense style questionnaire (DSQ, Andrews et al. 1993) was completed by 150 students and among those who had the required conditions to participate in the study, 30 students were randomly selected and divided into the control (n = 15) and experimental (n = 15) groups. Eight sessions of the REBT were conducted on the experimental group. Data were analyzed using ANCOVA analysis with the SPSS software version 20. Results: Results showed that after the interventions, a significant relationship was found between the control and experimental groups in terms of using mature and immature defense mechanisms (P < 0.05). However, the relationship between the control and experimental groups was not significant in terms of the neurotic defense mechanism (P > 0.05). In this regard, the rational emotive behavioral group counseling leads to reduction of using immature defense mechanisms (F (1,2)= 43.55, P = 0, ηp 2= 0.67) and increase using of mature defense mechanisms (F (1,2)= 19.78, P = 0, ηp 2= 0.42) among the students. Conclusions: The results of the current study indicate that the REBT therapy can balance and improve defense mechanisms among male high school students.